Analisis Proses Komunikasi POLRESTA Padang dalam Upaya Pencegahan PUNGLI di Pantai Padang Untuk Meningkatkan Transparansi Pelayanan Publik - Oktaviardi, Nadia; Eriend, Dion (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The Communication Process is a set of rules and stages in conveying information so that the message meets the target. Communication is one of the most important efforts in making policies and regulations as well as efforts to prevent illegal levies that occur on Padang Beach. The prevention efforts carried out by the Padang POLRESTA in dealing with cases of illegal levies (PUNGLI) which continuously occur along the Padang coast are a rule and a form of method or policy that is carried out to direct energy and thoughts to achieve a goal. The case of illegal levies has been one of the cases that has been quite difficult to handle from the past until now, this is because there have not been any witnesses who can incriminate the perpetrator enough to feel the deterrent effect of the act committed. In this prevention effort, the Padang POLRESTA is the main person responsible for the Padang City Government, assisted by the Satpol PP when there are field raid activities. Efforts were made such as raising awareness about the prohibition of illegal levies (PUNGLI) both in print and online media and also carried out directly by car using TOA as a loudspeaker to inform about the prohibition of illegal levies (PUNGLI). This direct appeal was made along the Padang coast because apart from providing information on the prohibition of illegal levies (PUNGLI), it also educated the public. The research method used in this research is qualitative with a descriptive approach and uses Joseph Devito's theory. The results of this research are to see how the communication process is carried out by the Padang POLRESTA in an effort to prevent extortion cases that occur on Padang Beach to increase the transparency of public services.